2015
DOI: 10.1016/j.jvs.2015.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Association between gender and outcomes of lower extremity peripheral vascular interventions

Abstract: Whereas we observed higher rates of access site complications including hematoma and occlusion in women, we found no other evidence for gender disparity in reinterventions, major amputation, or survival rates after PVI for patients with claudication or CLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 25 publications
(31 reference statements)
2
27
1
Order By: Relevance
“…Allcause mortality was in line with other similar recent surveys, and a diagnosis of IC was associated with improved overall survival compared with CLI (12-month mortality of 3% vs 20%; Fig 1). 23 Strikingly, our reported mortality data were also similar to a previous Swedish study preformed in 1970 to 1994. 24 By contrast, coronary heart disease mortality in Sweden decreased by 67.4% in men and 65.1% in women between 1987 and 2009.…”
Section: Discussionsupporting
confidence: 88%
“…Allcause mortality was in line with other similar recent surveys, and a diagnosis of IC was associated with improved overall survival compared with CLI (12-month mortality of 3% vs 20%; Fig 1). 23 Strikingly, our reported mortality data were also similar to a previous Swedish study preformed in 1970 to 1994. 24 By contrast, coronary heart disease mortality in Sweden decreased by 67.4% in men and 65.1% in women between 1987 and 2009.…”
Section: Discussionsupporting
confidence: 88%
“…Although there was no difference in length of stay, the median hospitalization cost was higher in males. These findings are contrary to previously published data, which suggested higher complications and mortality in females with PAD compared to males, although those studies had very small sample sizes . Our study reports data from a nationally representative sample with a significantly larger sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Women with PAD are more likely to be treated on the emergent basis . Women have higher mortality than men during management . However, these studies had small sample size.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There was no significant difference in death, major or minor complications between women and men [59]. In an observational study, Ferranti et al found no sex disparity in common femoral artery endarterectomy or arterial segment interventional treatment (Aortoiliac, Superficial femoral artery popliteal bypass, Infrapopliteal, Multiple grafts) [60]. With regard to infrainguinal disease, there are multiple conflicting results.…”
Section: Surgical Interventionmentioning
confidence: 99%